PENGGUNAAN TANAMAN Vetiveria zizanoides L. DAN BIOCHAR UNTUK REMEDIASI LAHAN PERTANIAN TERCEMAR LIMBAH TAMBANG EMAS - Hamzah, A.; Kusuma, Z.; Utomo, W.H.; Guritno, B. (BUANA SAINS, 2012)
Degradation of agricultural soils is not only due to application of over dose fertilizers and pesticides, but also industrial and mining activities. In Indonesia there are 713 spots of small scale gold mining surrounding agricultural land, and the process of amalgation is potential for heavy metal pollution. The aim of this study was to evaluate the use of Vetiveria zizanoides L and biochar to remediate soils contaminated with small scale gold mine tailings containing Hg and Pb.. The results indicated that soil pH decreased from 9,1 to 6-7 due to micing FeSO4 into cow manure and biochar, and also increased soil C-organic, N, P, K and CEC. Vietiveria zizanoides grown in the tailing medida showed capability to absorb Hg and Pb from the soil and stored in the root (Hg 88,91% and Pb 51,17%), leaves (Hg 11.09% and Pb 48.83%)